Relocating “Stuffed” Animals: Photographic Remediation of Natural History Taxidermy - Turner, Stephanie S. (Humanimalia, 2013)
This essay focuses on the remediating effects of photography of natural history museum taxidermy. How do these works refigure the apparent verisimilitude of taxidermied animals and their realistic diorama “habitats”? And how do they implicate viewers? Applying historian and curator Rachel Poliquin’s typology of taxidermy to a number of examples, I show how the “talkative thingness” of taxidermied animals — their tendency to signify in excess of their materiality — is expressed in the overlapping descriptive, biographical, cautionary, and experiential aspects of a number of contemporary photographers of natural history museum taxidermies.